QSAR for analogs of 1,5-N,N'-disubstituted-2-(substituted benzenesulphonyl) glutamamides as antitumor agents - Panda, Parthasarathi (2015)
Motivation. Cancer is a widespread and life threatening disease for which new and improved drugs are needed. It is well established that the transformation of the normal cells to a cancerous phenotype is often associated with cognate changes in the transport and metabolism of nutrients such as glucose and glutamine. Many tumor cells are particularly avid glutamine consumers. Glutamine also plays a key role in tumor cell energetics, and several tumor cell lines use glutamine as their major respiratory fuel. Method. Based on our composite program of development of new potential anticancer agents through rational design, 32 analogs of 1,5–N,N'–disubstituted–2–(substituted benzenesulphonyl) glutamamide were synthesized, characterized and biologically evaluated against Ehrlich Ascites Carcinoma (EAC) cells in Swiss Albino mice. Tumor cell inhibition was considered as the biological activity parameter. A QSAR study was performed on this data set, showing the importance of ETSA and RTSA indices of several atoms, the energy of HOMO, the energy gap between HOMO and LUMO, as well as the approximate surface area. Results. The QSAR study highlights the atomic features and molecular descriptors that determine the antitumor activity of these glutamamides analogs. These computational models also illustrate the importance of atomic charge, energy of HOMO, and energy of LUMO for the biological activity.